Fourteenth General Review of Quotas : Further Considerations. (Policy Papers; Policy Paper, 2010)
This paper provides the basis for the next round of discussions on the 14th General Review of Quotas. The Committee of the Whole (COW) has so far met three times this year: in March and July to consider the realignment of quota shares, and in April for an initial discussion on the size of the overall increase. Directors also met informally with the Managing Director on July 22 to take stock of the remaining issues, keeping in mind the tight timetable for completing the review and the need for flexibility and compromise from all sides. As discussed at the informal meeting, the Board recess provided an opportunity to take stock of the different positions and seek guidance from capitals on possible ways forward, with the goal of reaching a pragmatic solution that could bridge the remaining gaps within the relatively short period of time still available.